Performance and ruminal microbial and metabolic development of young calves fed diets containing aspergillus oryzae extract - A.A. Beharka; J.L. Morrill; Tiruvoor G. Nagaraja (Kansas Agricultural Experiment Station Research Reports, 1990)
Seventy-three, neonatal, Holstein, heifer calves in one experiment and 45 neonatal, Holstein, bull calves in another were used to study the effects of dietary Aspergillus oryzae extract (Amaferm) on calf performance. Forty of the heifer calves were selected to study the effects on ruminal microbial and metabolic development. In general, Amaferm-supplemented calves had greater ruminal microbial activity than the calves fed no Amaferm. For the most part, growth and feed intake were not affected.; Dairy Day, 1990, Kansas State University, Manhattan, KS, 1990; The 1990 Annual KSU Dairy Day is known as Dairy Day, 1990
Keywords: Dairy Day; 1990; Kansas Agricultural Experiment Station contribution; no. 91-148-S; Report of progress (Kansas Agricultural Experiment Station); 608; Dairy; Calves; Performance; Aspergillus oryzae